The Withering State Debate: Evidence From Malaysia's And Vietnam's Globalising Economies - Jandl, Thomas (Penerbit Universiti Sains Malaysia (USM Press), 2009)
It has been frequently argued that under globalisation, the state's ability to make autonomous decisions declines and the state withers away as it adapts to the lowest common denominator of taxation and social services in order to attract global investment flows. This paper challenges the withering-state theory. States are not hapless victims of globalisation, but active facilitators. Through the case studies of Vietnam and Malaysia, it is demonstrated that the state makes decisions about globalisation—either to engage in it or to retreat from it—based on the state's perceived interest. Moreover, the state is perfectly capable of reversing these decisions as state interests change over time